Comparative Analysis of Noise Reduction in Complex Mammogram Images Using Filters: A Preprocessing Stage - Sameer Saxena, Yudhveer Singh, Basant Agarwal (International Journal of Advanced Science and Technology, 2020)
There are many types of the cancers like lung cancer, blood cancer, liver cancer etc but the most common cancer in India is breast cancer. Mammography is a screening tool that is used to detect and diagnose the breast cancer. This technique is a particular form of breast imaging that uses low-intensity X-rays to diagnose cancer in its nascent stages before women feel the symptoms but the presence of noise in digital mammogram images can directly affect the integrity of the role of classification. It is important to eliminate noise in order to obtain correct images. The accuracy of predicting tumor depends primarily on the effectiveness of denoising techniques. Throughout the field of image processing, various types of denoising algorithms are used to smooth the surface of the image output and to eliminate unnecessary noise. The goal of the paper is to list the types of noise and their effect on the images and how the noise that is present in the image can be eliminated with the aid of filters and eventually increase the image quality of the mammogram. Keywords: Filters, Noises, Mammogram, PSNR, MSE.